Tipe Kepribadian Bigfive Dengan Pengambilan Keputusan Dalam Memilih Parfum di Kota Pekanbaru - Bima Maulana Putra; Fikri .; Suroyo . (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2021)
Decision making in buying a product is a difficult thing for consumers, because it really depends on the type of personality which belongs to consumers. Several studies explain that the personality type of big five is a variable that could influence decision making. The aim of this research is to explain the correlation between personality types of bigfive with decision making in choosing perfumes. The research population is perfume consumers in Pekanbaru Mall with a total of 400 consumers. Data were collected using BigFive Personality inventory scale and Decision Making scale. The sample was taken using accidental sampling technique. The analysis technique that was used in this research is Product Moment correlation test analysis techniques. Based on the analysis, there is correlation between Bigfive personality and decision making in choosing perfumes with a correlation value (r) of (0.839) with a significant value (p) of (0.035) (p<0.050). The hypothesis of this research is accepted, which means there is positive and significant correlation between personality type of bigfive and decision making in choosing perfumes. The effective contribution of BigFive Personality with Decision Making is 32.9%